Oxford handbook of reproductive medicine and family planning - McVeigh, Enda; Homburg, Roy; Guillebaud, John (Oxford University Press, 2013)
This handbook provides practical, evidence-based guidance on the care of adolescents, reproductive age females, and males. It follows chronological age up to the menopause, covering areas such as the reproductive system, puberty, the menstrual cycle, contraceptive methods, and infertility.